BENTUK PERTUNJUKAN WAYANG BOCAH SRIKANDHI KRIDHA KARYA JONET SRI KUNCORO - Pamungkas, Chrisnar Bagas; Daryono, Daryono (Greget: Jurnal Kreativitas dan Studi Tari, 2021)
The Wayang Bocah Srikandhi Kridha show was a dramatical production directed by Jonet Sri Kuncoro that displayed in 36th anniversary celebration of Soerya Soemirat dance studio. The problem with study is how the processing and appearance of the Srikandhi Kridha by Jonet Sri Kuncoro. Based on objects studied, this study uses a qualitative method with a process and shape approach. To find out about the garging process use the thinking of Rahayu Supanggah that include of materi garap, penggarap, sarana garap, perabot garap, penentu garap, pertimbangan garap. Discuss problem forms using concept forms by Rustopo in Sri Rochana Widyastutieningrum about elements that include of structure of a presentation, variety of motion, dance music, makeup and clothing, division of a single dancer and group, dance floor, property, and stage pattern. Studies have shown that a Srikandhi Kridha feature in a dramatic dialogue with the genre of Wayang Orang (bocah), one that concerns materi garap, penggarap, sarana garap, perabot garap, penentu garap, pertimbangan garap. The Wayang Bocah Srikandhi Kridha show set out from director’s concern for the child's world understanding of the puppet story. From reflection of his thought, Jonet took the play of the story with Srikandhi Kridha. Played by students of Soerya Soemirat dance studio. The shape of a Wayang Bocah Srikandhi Kridha show can be seen from all the performance being made into a solid outfit.Keywords: Wayang Bocah, garap, and form.